2013
DOI: 10.1098/rspb.2013.0647
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of mutation rate in an antagonistic coevolutionary model with maternal transmission of parasites

Abstract: By constantly selecting for novel genotypes, coevolution between hosts and parasites can favour elevated mutation rates. Models of this process typically assume random encounters. However, offspring are often more likely to encounter their mother's parasites. Because parents and offspring are genetically similar, they may be susceptible to the same parasite strains and thus, in hosts, maternal transmission should select for mechanisms that decrease intergenerational genetic similarity. In parasites, however, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 36 publications
5
15
0
Order By: Relevance
“…With stronger selection (such as with higher levels of virulence), the minimum strength of familial transmission needed to eliminate cycles is somewhat higher, but still surprisingly small. This result is consistent with what was found by Greenspoon and M'Gonigle (2013), who studied a mixed vertical and horizontal transmission matching-matching alleles system (see their Fig. 2A).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…With stronger selection (such as with higher levels of virulence), the minimum strength of familial transmission needed to eliminate cycles is somewhat higher, but still surprisingly small. This result is consistent with what was found by Greenspoon and M'Gonigle (2013), who studied a mixed vertical and horizontal transmission matching-matching alleles system (see their Fig. 2A).…”
Section: Discussionsupporting
confidence: 93%
“…Here, we present one‐ and two‐locus models in which a host individual can be infected either by a parasite strain infecting a genotypically similar host, or from a strain infecting a randomly selected host. This differs from a mixed vertical and horizontal transmission model (e.g., Greenspoon and M'Gonigle ) because our model permits preferential transmission from any genetically similar individuals in the previous generation, not only transmission from mother to offspring (vertical transmission). Besides adding generality to the model, this also has the added advantage of simplifying the model, and permitting an analytical understanding of cycles, which was not possible in the model of Greenspoon and M'Gonigle ().…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…This approach allows us to investigate nonrandom parasite transmission. Similar approaches have been used to evaluate the effect of maternal transmission on the evolution of sex (Agrawal ) and the evolution of mutation rate (Greenspoon and M'Gonigle ).…”
Section: Modelmentioning
confidence: 99%
“…). Recent theoretical work has shown that maternal transmission of parasites changes predictions about the evolution of sex (Agrawal ) and mutation rate (Greenspoon and M'Gonigle ). Maternally transmitted parasites tend to be genetically well targeted to offspring by virtue of the genetic similarity between mother and offspring.…”
mentioning
confidence: 99%